Perilaku Keuangan Menabung Mahasiswa Rantau Fakultas Ekonomi dan Bisnis UPN “Veteran” Jawa Timur - Astimeyra, Dhea Nanda; Nur, Dhani Ichsanuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The ability to manage finances effectively is crucial for students living away from home, as they must manage their own budgets while meeting various academic and personal needs. This study aims to analyze the relationship between financial literacy, lifestyle, and financial attitudes toward saving behavior among students of the Faculty of Economics and Business at UPN